Farming and incidence of motor neuron disease: French nationwide study. (20th July 2017) - Kab, S.; Moisan, F.; Elbaz, A.
Abstract : Background and purpose: The association of farming with motor neuron disease (MND) is unclear, with conflicting studies. We performed a French nationwide study of the association of farming with MND incidence, and compared findings with those for Parkinson's disease (PD), which has been shown to be more frequent in farmers. Methods: We used the French national health insurance and hospital discharge databases to identify MND/PD incident cases. The Mutualité Sociale Agricole (MSA) guarantees health insurance for farmers and agricultural workers. We compared the incidence of MND (2010–2014) and PD (2011–2012) in MSA farmers, MSA workers and non‐MSA affiliates, and estimated relative risks (RRs) and 95% confidence intervals (CIs). Probabilistic sensitivity analyses were used for external smoking adjustment. Results: Analyses relied on 8931 MND (MSA, 9%) and 45 409 PD (MSA, 11%) cases. There was a trend towards higher MND incidence in MSA farmers compared with non‐MSA affiliates (RR, 1.08; 95% CI, 0.99–1.18) and MSA workers (RR, 1.13; 95% CI, 0.97–1.31) that strengthened after smoking adjustment (if associated with MND). PD incidence was higher in MSA farmers than non‐MSA affiliates (RR, 1.13; 95% CI, 1.08–1.17) and MSA workers (RR, 1.10; 95% CI, 1.02–1.18); this association remained after smoking adjustment (RR, 1.09; 95% CI, 1.05–1.14). Conclusions: This French nationwide study suggested an association between farming and MND, and confirmed higher PD incidence in farmers in France, a country with high pesticide use.